Genesis of tourmalinite from Chitral, Northern Pakistan - Zahid, Mohammad; Moon, C.J. (Journal of Himalayan Earth Sciences, 1999)
Miniki Gol scheelite-bearing tourmalinite occurs within the Jurassic Arkari Formation. The Arkari Formation is located near the Pak-Afghan border within the Eastern Hindu Kush and is composed of garnet mica schist, phyllite, marble, mica quartzite, calc-silicate quartzite and subordinate tourmalinite. The extension of tourmalinite is vet)’ limited and has been identified at three locations within the mica schist. Tourmalinite is dominantly composed of tourmaline, spessartine-rich garnet, quartz and scheelite. Tourmaline reaches up to by volume in some tourmalinites. The chemical composition of tourmaline and garnet of the tourmalinite fairly corresponds with those of the nearby exposed leucogranite. The values of K2O, MnO, Zn, Rb and Ba of Miniki Gol tourmalinite, are not markedly different from the associated schist and thus cannot be considered as siliceous chemical precipitates (exhalites). The limited extension of the tourmalinite is also inconsistent with the occurrence of exhalites. The lack of Sb, Hg, Ag, F and P in the tourmalinite also rules out the possibility of the exhalative activity in the study area. A linear relationship between LREE and elements of obvious igneous origin such as Zr, Hf and Be in the tourmalinite indicates a post-magmatic metasomatic activity. The Miniki Gol leucogranite can be considered as potential source for the extreme enrichment of boron in the tourmalinite.